The Closing of the American Mind and The Trial of Socrates by Allan Bloom and I. F. Stone, Reviewed by Richard Mial - Mial, Richard (Analytic Teaching, 2014)
Introduction: University of Chicago Professor Allan Bloom presents the self-directed learner with what might be an unanswerable dilemma. On the one hand, he seems to argue, in his book, The Closing of the American Mind, that one of the reasons why American higher education is in such a sorry condition is because we have abandoned the great books, Plato, Aristotle, Rousseau, et al, at least in part because the writers were either too white, too male, too Western, or simply irrelevant to these changing times in a multi-cultural world.